2009
DOI: 10.5271/sjweh.1362
|View full text |Cite
|
Sign up to set email alerts
|

Fate of abstracts presented at an International Commission on Occupational Health (ICOH) congress – followed by publication in peer-reviewed journals?

Abstract: Refers to the following text of the Journal: 2007;33(4):245-251The following articles refer to this text: 2010;36(6): 484-487; 2011;37(6):494-501

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
4
1
1
Order By: Relevance
“…This median time to publication was lower than those recorded in previous studies (21,22). In the previous investigations, search for published articles was conducted two years after the congress (4,6,8), while this time was 12 months for the current survey.…”
Section: Discussioncontrasting
confidence: 38%
“…This median time to publication was lower than those recorded in previous studies (21,22). In the previous investigations, search for published articles was conducted two years after the congress (4,6,8), while this time was 12 months for the current survey.…”
Section: Discussioncontrasting
confidence: 38%
“…To identify the studies that worth to be included in a systematic review, we relied on the works of the experts used as reviewer in the systematic reviews we included, since all of them used at least 2 independent reviewers. Furthermore, we excluded from our gold standard database personal communications, because they cannot be retrieved by any database, and abstracts because it has been clearly demonstrated that such abstracts often display non-valid results [21,22]. Considering the methods used by the authors of the systematic reviews we selected, the use of at least two independent reviewers to select relevant articles in these reviews, the high number of databases searched and the absence of restriction to English studies in each of them, we can also assume that, for each topic covered, all the relevant studies were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Abstracts presented in congress or meetings that were already included in the Cochrane systematic review were excluded from our gold standard database since it has been clearly demonstrated such abstracts often display invalid results (11,12). Therefore, we can assume that our database really included all the high quality studies relevant to the topics covered by the systematic reviews and only high-quality studies.…”
Section: Discussionmentioning
confidence: 99%